EFL Teachers’ Views about The Application of Collaborative Learning at Addis Ababa Science and Technology University, Ethiopia - Lemma, Befikadu (Jurnal Paedagogy, 2024)
This study aims to investigate teachers’ views about the implementation of collaborative learning in English classes. Collaborative learning helps students to improve their English language performance. The data was collected through observation, questionnaires, and interview. The quantitative data were analyzed using percentage and frequency. Theme analysis technique was used to analyze the qualitative data. The result of the study indicated that most EFL teachers widely implement students’ collaborative learning, but the type of collaborative learning they are implementing is not collaborative group learning. Most of the teachers simply make their students to sit side by side to talk with each other as they do their individual assignments, and some teachers assign a task to groups.  Then, one or two of the group members do the work and the other group members get equal credit. Although each of these is important in collaborative learning, they do not qualify collaborative learning rather traditional group learning. The data obtained from teachers’ interview revealed that teachers widely implement both informal and base group collaborative learning since most of the teachers allow their students to work collaborative from few minutes to a class period and most of the groups (‘Net works’) formed are with stable membership for the semester. In addition to this, some teachers were not playing their roles as they are expected. Teachers and other concerned bodies ought to deliver sorts of orientations to the students about the importance of collaborative learning to maximize their views before implementing collaborative learning.